Analisis Yuridis Pertanggung Jawaban Pidana Terhadap Tindak Pidana Penadahan Di Dalam Kuhp - Edgar, Calvin; Firmansyah, Hery; Hum, M. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The criminal act of fencing in Dutch is called Heling, which is a serial crime, which means that the crime is a follow-up crime related to the predicate crime. Basically, the crime of collection does not stand alone, but is a crime that begins with a predicate crime, so whether or not a person is suspected of committing a crime of collection, it must first be clear what the predicate crime is, this is a condition for determining in advance. whether the goods he obtained were from crime or not. seen from the point of being responsible, only someone who is capable of being responsible can be held accountable for his actions. what he gets is the proceeds of crime, which often happens in society. Law enforcement that is created is directed at efforts to strengthen the law by realizing justice and certainty by harmonizing legal needs in society itself.